The fine implicative structure of European Portuguese conjugation - Sacha Beniamine; Olivier Bonami; Ana R. Luís (Isogloss, 2021)
Recent literature has highlighted the extent to which inflectional paradigms are organised into systems of implications allowing speakers to make full use of the inflection system on the basis of exposure to only a few forms of each word. The present paper contributes to this line of research by investigating in detail the implicative structure of European Portuguese verbal paradigms. After outlining the computational methods we use to that effect, we deploy these methods on a lexicon of about 5000 verbs, and show how the morphological and phonological properties of European Portuguese verbs lead to the observed patterns of predictability.